Use of clinical staging in amyotrophic lateral sclerosis for phase 3 clinical trials - Balendra, R; Jones, A; Jivraj, N; Steen, I; Young, C; Shaw, P; Turner, M; Leigh, P; Al-Chalabi, A (BMJ Publishing Group, 2015)
Objectives: The use of clinical staging in the fatal neurodegenerative disease amyotrophic lateral sclerosis would have value in optimising future therapeutic trials. We aimed to use previous clinical trial data to determine the length of time patients spend in each of four proposed stages, its range and transition patterns to subsequent stages. Methods: Using databases from two multicentre clinical trials, patients were retrospectively staged through the trial course. At each stage we assessed whether patients then progressed to an earlier, consecutive or later stage or death. Duration spent in each stage before progression to a later stage was calculated. Results: There were 725 patients. No patients moved to an earlier stage. More patients at stages 1, 2 and 3 progressed to the consecutive stage rather than skipping a stage. 59.3% of patients at Stage 1 progressed to Stage 2, 54.0% of patients at Stage 2 progressed to Stage 3, 42.3% of patients at Stage 3 progressed to Stage 4 and 47.0% of Stage 4 patients progressed to death. Transition times between stages had a median duration of 3 to 7 months for stages 2 to 4. Discussion: We have shown using trial data that transition times between stages are short. Use of stage duration as an endpoint might allow a shorter trial duration. We have shown face validity in this system as most patients progress through consecutive stages, and none revert to earlier stages. Furthermore, we have shown the system is reliable across populations and therefore has content validity.